Numerical study of 3D gravity current flows - Leow Soon Kit (2023)
This study describes the development of gravity current which is one of the immense interest to researchers due to the great impact of gravity current on natural phenomena or industrial scenario. In this present thesis, gravity current are studied by using direct numerical simulations (DNS) through computational fluid dynamic software (CFD), OpenFoam on computing platforms.